3D Printed Nanophotonic Waveguides. Issue 8 (30th May 2016) - Pyo, Jaeyeon; Kim, Ji Tae; Lee, Junho; Yoo, Jewon; Je, Jung Ho
Abstract : 3D integration of photonic nanowire waveguides is demonstrated by a precise and versatile meniscus‐guided 3D nanoprinting method. By realizing 3D direct linking of nanophotonic elements with no substrate leakage and, moreover, excellent stretchable operations (>50%), 3D functional photonic components of multiplexers and splitters are demonstrated finally.